Decreasing predation levels and increasing landings challenge the paradigm of non-management of North Sea brown shrimp (Crangon crangon). (26th November 2014) - Temming, Axel; Hufnagl, Marc
Abstract: The North Sea brown shrimp fishery is currently regulated neither with quotas nor with effort management. The current paradigm of non-management was based on an analysis of the total predation by cod and whiting in relation to commercial catches for the period 1970–1995 and the estimated total dominance of natural mortality. However, since this period, the North Sea ecosystem has undergone pronounced changes with overfishing and climate change causing a substantial decline in predator stocks, namely cod and whiting. In addition, both predators have shifted their range of distribution causing a reduced overlap with brown shrimp. Here, we extend the previous assessment of brown shrimp predation for the years 1996–2011 using updated stock assessment and predator distribution data. For the first time, predation estimates are used together with commercial landings to partition independent estimates of total mortality into fishing and predation mortality. We demonstrate that the decline of key predators of brown shrimp in combination with a shift in the distributional range of the predators has caused a new situation, in which the fishery has become the main mortality source of adult brown shrimp (>50 mm). Average landings since 2000 have been ∼40% higher than in the 1980s and 1990s, indicating that humans have at least partly taken over the share previously taken by juvenile whiting and cod. We discuss that this situation is likely to continue, because three marine mammal species have built up a combined population of over 80 000 individuals, which hunt for potential brown shrimp predators mainly in the distribution area of brown shrimp. The application of two yield-per-recruit models of different complexity indicates potential growth overfishing of brown shrimp and reopens the discussion of management.